Rare Histological Variants of Liver Cancer and Their Management: A Single-Institution Experience. (21st April 2021) - Swed, Brandon; Gandarilla, Omar; Chiu, Kenrry; Halazun, Karim H.; Samstein, Benjamin; Yantiss, Rhonda; Brar, Gagandeep
Abstract : Primary liver malignancies, including hepatocellular carcinoma (HCC) and cholangiocarcinoma, are a major cause of cancer-related morbidity and mortality worldwide. There are several histologically and biologically distinct subtypes of liver cancer that have previously been reported. However, literature regarding the nonsurgical management of these patients upon disease recurrence remains limited. These variants include combined HCC-cholangiocarcinoma (cHCC-CC), Epstein–Barr virus- (EBV-) associated carcinoma, undifferentiated carcinoma, and clear cell or thyroid-like variants of HCC. Here, we aim to highlight the pathologic features, clinical course, and outcomes of five patients with these unusual hepatic tumors and explain the rationale behind the choice of their systemic therapies upon disease recurrence. All patients underwent surgical resection as the standard of care for localized disease, and upon relapse, they were treated with either chemotherapy, targeted therapy, immunotherapy, or active surveillance based on the clinical context and tumor histology. These rare variants are important to recognize as they have prognostic and therapeutic implications, and there are currently insufficient data in the literature to guide further therapy.